Microstructure, dielectric properties and optical band gap control on the photoluminescence behavior of Ba[Zr0.25Ti0.75]O-3 thin films - Cavalcante, L. S.; Sczancoski, J. C.; Vicente, Fábio Simões de [UNESP]; Frabbro, M. T.; Li, M. Siu; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer, 2009)
Ba[Zr0.25Ti0.75]O-3 (BZT) thin films were synthesized by the complex polymerization method and heat treated at 400 A degrees C for different times and at 700 A degrees C for 2 h. These thin films were analyzed by X-ray diffraction (XRD), Fourier-transform infrared (FT-IR) spectroscopy, field emission gun-scanning electron microscopy (FEG-SEM) and atomic force microscopy (AFM), Ultraviolet-visible (UV-vis) absorption spectroscopy, electrical and photoluminescence (PL) measurements. FEG-SEM and AFM micrographs showed that the microstructure and thickness of BZT thin films can be influenced by the processing times. Dielectric constant and dielectric loss of BZT thin films heat treated at 700 A degrees C were approximately 148 and 0.08 at 1 MHz, respectively. UV-vis absorption spectra suggested the presence of intermediary energy levels (shallow and deep holes) within the band gap of BZT thin films. PL behavior was explained through the optical band gap values associated to the visible light emission components.
Keywords: Microstructure; Dielectric; Optical band gap; Photoluminescence; BZT thin films